Effects of Physical Education Interventions on Cognition and Academic Performance Outcomes in Children and Adolescents: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (BMJ Publishing Group, 2021)
Objective To determine the effects of interventions aimed at optimising the quantity and quality of physical education (PE) on cognition and academic performance in children and adolescents. Design A systematic review and meta-analysis. Data sources Studies from electronic databases from inception to 3 January 2021 were identified. Eligibility criteria for selecting studies Experimental studies that assessed the effect of quantity-based (ie, increasing the amount of curriculum time allocated to PE) or quality-based (ie, increasing students participation in physical activity during PE) PE interventions, or both, on changes in cognition and/or academic performance in youth (aged 5-18 years) were included. Results 19 trials comprising 8676 youth (46.5% girls) were included. Individual quality-based PE interventions increased cognition performance (Hedges g=0.38, 95% CI 0.15 to 0.60; I 2 =83.70%), mainly in primary education settings (g=0.48, 95% CI 0.07 to 0.89; I 2 =90.43%). Academic performance, principally mathematics-related skills, was also increased by quality-based PE interventions (g=0.15, 95% CI 0.06 to 0.24; I 2 =41.75%). Among these interventions, teaching strategies favoured similar results, but without heterogeneity in the results (g=0.12, 95% CI 0.05 to 0.18; I 2 =0%). In contrast, quantity-based PE interventions had a very small and non-significant effect on academic performance (g=0.09, 95% CI-0.05 to 0.24; Q=11.65; I 2 =48.48%). Finally, there were no differences between the three PE interventions (ie, quantity, quality, and combined PE interventions) in regard to academic performance. Conclusion Improving the quality of PE classes may improve students cognition and academic performance in children and adolescents. Importantly, allocating more time for PE does not seem to compromise this performance. © 2021 Author(s). Published by BMJ.